Mozambique : Country Financial Accountability Assessment - World Bank (Washington, DC, 2013)
The overall conclusion of this country financial accountability assessment report is that public sector financial management systems in Mozambique are very weak, as evidenced by the Reports of the Tribunal Administrative (TA) on the General State Accounts for 1998 and 19992, and will require substantial strengthening over several years. In the interim, risks of waste, diversion and misuse of funds are assessed as high. This has clear implications for both the Government and its donors: (a) the Government will need to address the main issues identified for improvement in the Report in the aim of establishing practices and standards on a par with international benchmarks3; and (b) the donors will need to support this process and, in the meantime, to build explicit risk minimization actions and conditionality into their Mozambican operations.. Recommended actions to improve public financial management include: enacting and implementing public financial management laws; strengthening public sector auditing capacity; strengthening financial management in local government; developing the accountancy profession; and strengthening/expanding programs in higher education institutions.